Cytotoxicity Effects of Vitamin C on Cancer Cells MCF-7 - Endang Purwaningsih; Samsul Mustofa; Pendrianto (Nusantara Science and Technology Proceedings, 2021)
Vitamin C (ascorbic acid) is a powerful antioxidant that can reduce the effects of oxidative stress. One of the diseases caused by oxidative stress is cancer. The study aimed to assess the cytotoxic effect of vitamin C on MCF7 cancer cell cultures. This study used an in vitro laboratory experiment using MCF-7 breast cancer cell culture. MTS assay method was used to test the dose variance of vitamin C (l-ascorbic acid) against MCF-7 cultures. The MTS test used the CellTiter 96 Aqueous One Solution Cell Proliferation Assay kit. After that, 24 and 48 hours of culture were observed using test doses, 0 (negative control, K(–)), 10, 20, 40, 80, 160, 320 g/mL. The results showed the higher the dose given, the lower the viability of MCF7 cells, both at 24 and 48 hours of incubation. The lowest viability was obtained at 86.75% at a dose of 320 g/mL during incubation for 24 hours and 7.95% at a dose of 320 g/mL during incubation for 48 hours. In conclusion, vitamin C has a cytotoxic effect on MCF-7 cell culture with an IC50 value of 140 g/mL. Further research is needed to determine the effectiveness of vitamin C on the expression of the telomerase enzyme in breast cancer cells, especially MCF-7.